ANALISIS PERHITUNGAN BIAYA KUALITAS STANDARISASI INFRASTRUKTUR LABORATORIUM DI KABUPATEN DONGGALA - Irawati, Sri Wahyuni (Katalogis, 2017)
Laboratory testing conducted by The Department of Public Works aims to achieve accurate quality of materials in supporting infrastructure development, particularly in works such as roads, bridges, and buildings, Laboratory testing consists of materials like soil, concrete and asphalt to be used in road works, brigdes, and building the country. Tests conducted in the laboratory of Department of Public Works consists of material testing soil, concrete and asphalt materials to  be use in road construction and building bridges. Product of these will be used as reference by counterparties or service users. Costs arising from the aktivitiesin the laboratory is the responsibility of the partners or the service users. Therefore, the Department of  public works as the relevant agency needs to set price rates for the partners,based on analysis of laboratory testing with regards to all activities in the laboratory. ABC method is a method of analysis that can be used in the calculation of tariff based on activities in the laboratorium.